2016
DOI: 10.1182/blood-2015-07-656678
|View full text |Cite
|
Sign up to set email alerts
|

UCH-L1 is induced in germinal center B cells and identifies patients with aggressive germinal center diffuse large B-cell lymphoma

Abstract: • The neuronal marker UCH-L1 is induced in, and specifically augments the oncogeneinduced transformation of, GCB cells.• High levels of UCHL1 identify patients with GC DLBCL with an increased risk for poor outcomes.Gene expression profiling has identified 2 major subclasses of diffuse large B-cell lymphoma (DLBCL). Cases resembling germinal center (GC) B cells (GCB-DLBCL) generally occur in younger patients, have a distinct molecular pathophysiology, and have improved outcomes compared with those similar to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…UCHL1 levels of expression and enzymatic activity are correlated with increased metastatic behavior in various cancers, including small‐cell lung cancer, myeloma, and lymphoma . Three cell lines were selected to evaluate the efficacy of compound 1 based on their sensitivity to genetic depletion of UCHL1: SW1271 (small‐cell lung cancer line), KMS11, and KMS12 (myeloma cell lines).…”
Section: Resultsmentioning
confidence: 99%
“…UCHL1 levels of expression and enzymatic activity are correlated with increased metastatic behavior in various cancers, including small‐cell lung cancer, myeloma, and lymphoma . Three cell lines were selected to evaluate the efficacy of compound 1 based on their sensitivity to genetic depletion of UCHL1: SW1271 (small‐cell lung cancer line), KMS11, and KMS12 (myeloma cell lines).…”
Section: Resultsmentioning
confidence: 99%
“…As a de-ubiquitination enzyme, UCH-L1 is considered as a tumor promoting protein in many human tumors. [16][17][18][19][20][21][22][23][24] However, the function of UCH-L1 in tumor initiation, progression and invasion is still controversial, as UCH-L1 has also been found to be downregulated in other tumor types including prostate cancer, 47 ovarian cancer, 48 and nasopharyngeal cancer. 49 Therefore, the potential role of UCH-L1 as an oncogene or a tumor suppressor may be cell context or tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…A series elegant in vivo studies from the same group also highlighted a role of UCH-L1 on activating Akt signaling through different molecular mechanisms without alterating expression level of total Akt protein. [18][19][20]57 In addition, many studies have demonstrated that regulation of Akt is mainly through caspase-mediated degradation and heat shock protein-mediated protein stabilization, while only few studies suggested Akt might be degraded by ubiquitin-proteasom system (UPS) (summarized in the review article 58 ). Thus, it is unlikely that UCH-L1 activates Akt signaling pathway by de-ubiquitinating and stabilizing Akt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Encoding a small (25 kDa) deubiquitinating enzyme, transgenic expression of Uchl1 is sufficient to drive spontaneous B-cell lymphomagenesis in mice and accelerate disease in the Em-myc model. 10,11 We uncovered a previously unrecognized function of UCH-L1 in reorganizing mTOR-AKT signaling both in cell lines and in mice. 12 UCH-L1 disrupts the ubiquitination of the mTORC1 subunit raptor that is required for its stable association with mTOR, leading to reduced levels of mTORC1.…”
Section: Introductionmentioning
confidence: 99%